'Ala' al-Dawla al-Simnani between spiritual authority and political power : a Persian lord and intellectual, in the heart of the Ilkhanate, With a critical edition and translation of al-Warid alsarid al-tarid subhat al-marid and a critical edition of its Persian version Zayn al-mu'taqad li-zayn al-mu'taqid - Martini, Giovanni Maria. (Islamicate Intellectual History, 2017)
In ʿAlāʾ al-Dawla al-Simnānī between Spiritual Authority and Political Power: A Persian Lord and Intellectual in the Heart of the Ilkhanate , Giovanni Maria Martini investigates the personality of a major figure in the socio-political and cultural landscape of Mongol Iran. In pursuing this objective, the author follows parallel paths: Chapter 1 provides the most updated reconstruction of Simnānī's (d. 736/1336) biography, which, thanks to its unique features, emerges as a cross-section of Iranian society and as a microhistory of the complex relationships between a Sufi master, Persian elites and Mongol rulers during the Ilkhanid period; Chapter 2 contains a study on the phenomenon of Arabic-Persian diglossia in Simnānī's written work, arguing for its socio-religious function; in Chapters 3 to 6 the critical editions of two important, interrelated treatises by Simnānī are presented; finally, Chapter 7 offers the first full-length annotated translation of a long work by Simnānī ever to appear in a Western language.